AML alters bone marrow stromal cell osteogenic commitment via Notch signaling - Tomasoni, Chiara; Arsuffi, Corinne; Donsante, Samantha; Corsi, Alessandro; Riminucci, Mara; Biondi, Andrea; Pievani, Alice; Serafini, Marta (Frontiers in Immunology, 2023)
Acute myeloid leukemia (AML) is a highly heterogeneous malignancy caused by various genetic alterations and characterized by the accumulation of immature myeloid blasts in the bone marrow (BM). This abnormal growth of AML cells disrupts normal hematopoiesis and alters the BM microenvironment components, establishing a niche supportive of leukemogenesis. Bone marrow stromal cells (BMSCs) play a pivotal role in giving rise to essential elements of the BM niche, including adipocytes and osteogenic cells. Animal models have shown that the BM microenvironment is significantly remodeled by AML cells, which skew BMSCs toward an ineffective osteogenic differentiation with an accumulation of osteoprogenitors. However, little is known about the mechanisms by which AML cells affect osteogenesis. We studied the effect of AML cells on the osteogenic commitment of normal BMSCs. Using a 2D co-culture system, we found that AML cell lines and primary blasts, but not normal hematopoietic CD34 + cells, induced in BMSCs an ineffective osteogenic commitment, with an increase of the early-osteogenic marker tissue non-specific alkaline phosphatase (TNAP) in the absence of the late-osteogenic gene up-regulation. Moreover, the direct interaction of AML cells and BMSCs was indispensable in influencing osteogenic differentiation. Mechanistic studies identified a role for AML-mediated Notch activation in BMSCs contributing to their ineffective osteogenic commitment. Inhibition of Notch using a γ-secretase inhibitor strongly influenced Notch signaling in BMSCs and abrogated the AML-induced TNAP up-regulation. Together, our data support the hypothesis that AML infiltration produces a leukemia-supportive preosteoblast-rich niche in the BM, which can be partially ascribed to AML-induced activation of Notch signaling in BMSCs.